Satisfaction with Continuous Glucose Monitoring in Pregnant Patients with Type 1 and Type 2 Diabetes - Shrestha, Kevin S.; Battarbee, Ashley N. (American Journal of Perinatology, 2024)
Continuous glucose monitoring (CGM) improves pregnancy outcomes in type 1 diabetes. Given the rapid uptake of CGM in pregnancies complicated by both type 1 and type 2 diabetes, our objective was to determine if CGM satisfaction and use differed between type 1 and type 2 diabetes.Cross-sectional survey study of 100 patients with pregestational diabetes who used Dexcom G6 CGM during pregnancy and received prenatal care at a single tertiary care center. Participants completed the validated 15-question Glucose Monitoring Satisfaction Survey (GMSS) and other questions about CGM use. The primary outcome was high satisfaction with CGM, defined as a total GMSS score of 4 or greater. Secondary outcomes included GMSS subscales, frequency of CGM app use, and CGM features used. Outcomes were compared between type 1 and type 2 diabetes, and logistic and ordinal regression estimated the association between type 2 diabetes and outcomes.Of 100 surveyed patients, 45 had type 1 and 55 had type 2 diabetes. Patients with type 1 diabetes were more likely to use CGM before pregnancy and use an insulin pump. CGM satisfaction did not differ between type 1 and type 2 diabetes (74.5 vs. 56.6%; adjusted odds ratio [aOR] = 0.54, 95% [confidence interval] CI: 0.21–1.36). High openness, low behavioral burden, low emotional burden, and high worthwhileness also did not differ between groups after adjustment for CGM use before pregnancy. Reported CGM app use was high and did not differ between groups. Patients with type 2 diabetes were less likely to use arrows and/or graphs on the CGM app compared to type 1 diabetes.In this cohort, patients with type 2 diabetes appear to be similarly satisfied with CGM compared to those with type 1 diabetes. Future efforts focused on CGM education for new users may help increase the use of CGM app features, maximize satisfaction, and minimize technology burden.
Keywords: pregestational diabetes; type 1 diabetes; type 2 diabetes; continuous glucose monitoring; satisfaction; survey; Glucose Monitoring Satisfaction Survey